Du Fu Transforms : Tradition and Ethics amid Societal Collapse - Bender, Lucas Rambo (Book collections on Project MUSE., 2021)
"Often considered China's greatest poet, Du Fu (712-770) came of age at the height of the Tang dynasty, in an era marked by confidence that the accumulated wisdom of the precedent cultural tradition would guarantee civilization's continued stability and prosperity. When his society collapsed into civil war in 755, however, he began to question contemporary assumptions about the role that tradition should play in making sense of experience and defining human flourishing. In this book, Lucas Bender argues that Du Fu's reconsideration of the nature and importance of tradition has played a pivotal role in the transformation of Chinese poetic understanding over the last millennium. In reimagining his relationship to tradition, Du Fu anticipated important philosophical transitions from the late-medieval into the early-modern period and laid the template for a new and perduring paradigm of poetry's relationship to ethics. He also looked forward to the transformations his own poetry would undergo as it was elevated to the pinnacle of the Chinese poetic pantheon"--